Upper limb and lower limb radiofrequency treatments in orthopaedics - E Carlos Rodríguez-Merchán; Alberto D Delgado-Martínez; Javier De Andrés-Ares (EFORT Open Reviews, 2023)
Radiofrequency (RF) is a minimally invasive technique for disrupting or altering nociceptive pathways to treat musculoskeletal neuropathic and nociplastic pain. RF has been employed to treat painful shoulder, lateral epicondylitis, knee and hip osteoarthritis, chronic knee pain, Perthes disease, greater trochanteric pain syndrome, plantar fasciitis, and painful stump neuromas; it has also been employed before and after painful total knee arthroplasty and after anterior cruciate ligament reconstruction. The benefits of RF include the following:it is safer than surgery; there is no need for general anaesthesia, thereby reducing adverse effects; it alleviates pain for a minimum of 3–4 months; it can be repeatable if necessary; and it improves joint function and minimizes the need for oral pain medication. RF is contraindicated for pregnant women; unstable joints (hip, knee, and shoulder); uncontrolled diabetes mellitus; presence of an implanted defibrillator; and chronic joint infection (hip, knee, and shoulder). Although adverse events from RF are unusual, potential complications can include infection, bleeding, numbness or dysesthesia, increased pain at the procedural site, deafferentation effect, and Charcot joint neuropathy. Although there is a risk of damaging non-targeted neural tissue and other structures, this can be mitigated by performing the technique under imaging guidance (fluoroscopy, ultrasonography, and computed tomography). RF appears to be a valuable technique for alleviating chronic pain syndromes; however, firm proof of the technique’s efficacy is still required. RF is a promising technique for managing chronic musculoskeletal of the limbs pain, particularly when other techniques are futile or not possible.